Effects of repetitive head impacts from a single season on the cognitive functioning of youth male soccer players - Watson, R.S.; Sergio, L.; Mao, H.; Brooks, J.S.; Dickey, J.P. (PLOS ONE, 2025)
Repetitive head impacts have long-lasting negative effects on the cognition of athletes. For example, repetitive head impacts accumulated by adult professional soccer players throughout their careers result in long-term negative consequences on cognition. However, these effects on youth soccer players have not been extensively studied and need to be further evaluated. The purposes of this study were to quantify head impact exposure in youth elite soccer and to examine the effects of repetitive head impacts on the cognitive function of youth male soccer players. A prospective cohort study of a single boys U13 soccer team of 18 players (12.9 ± 0.2 years of age) was completed throughout a single soccer season (five months in duration). Head impact frequency data were recorded using impact monitoring mouthguards worn during practices and matches and subsequently video-verified. Cognitive function was assessed using cognitive-motor integration (CMI) tasks conducted before the first season match, every subsequent four weeks, and after the last match. Peak path velocity, absolute error, reaction time, full path movement time, and the number of direction reversals were CMI task outcome measures. Over a single soccer season, 1089 head impacts occurred with more head impacts occurring in practices (62.7%) than matches (37.3%). Midfielders experienced the most head impacts during practices (53.6% of practice impacts), and defenders experienced the most head impacts during matches (47.8% of match impacts). Repetitive head impact exposure by position was associated with significant decreases in absolute error (p < 0.001), increases in peak velocity (p < 0.001), and increases in reaction time (p < 0.001). Repetitive head impacts within a single soccer season were associated with measurable declines in some aspects of youth soccer players` cognitive function. Therefore, coaches should aim to reduce the number of head impacts experienced by male youth soccer players with a specific focus on reducing head impact exposure during practices.